Application of Problem Based Learning Assisted by Google Classroom Application to Increase Student Interest in SDN 1 Wonoyoso Students - Desi Tri Widiyanti (Universitas Sebelas Maret, 2020)
The purpose of this research is to increase students' interest in learning. This research is a classroom action research (PTK) which was conducted in 3 cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were fourth grade students and fifth grade students of SD Negeri 1 Wonoyoso, Kuwarasan District, Kebumen Regency in the academic year 2020/2021, totaling 28 students. Data collection techniques using observation, questionnaires and tests. Data analysis includes data reduction, data presentation, and drawing conclusions. The research shows that the application of the Problem Based Learning learning model can increase the learning interest and learning outcomes of grade IV and grade V SD Negeri 1 Wonoyoso, Kuwarasan District, Kebumen Regency in the academic year 2020/2021 as evidenced by the percentage of completeness of learning outcomes in cycle Iamounted to 53.6% to 92.9% in cycle III